The Validity and Responsiveness of Isometric Lower Body Multi-Joint Tests of Muscular Strength: a Systematic Review - David Drake; Rodney Kennedy; Eric Wallace (SpringerOpen, 2017)
Abstract Background Researchers and practitioners working in sports medicine and science require valid tests to determine the effectiveness of interventions and enhance understanding of mechanisms underpinning adaptation. Such decision making is influenced by the supportive evidence describing the validity of tests within current research. The objective of this study is to review the validity of lower body isometric multi-joint tests ability to assess muscular strength and determine the current level of supporting evidence. Methods Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines were followed in a systematic fashion to search, assess and synthesize existing literature on this topic. Electronic databases such as Web of Science, CINAHL and PubMed were searched up to 18 March 2015. Potential inclusions were screened against eligibility criteria relating to types of test, measurement instrument, properties of validity assessed and population group and were required to be published in English. The Consensus-based Standards for the Selection of health Measurement Instruments (COSMIN) checklist was used to assess methodological quality and measurement property rating of included studies. Studies rated as fair or better in methodological quality were included in the best evidence synthesis. Results Fifty-nine studies met the eligibility criteria for quality appraisal. The ten studies that rated fair or better in methodological quality were included in the best evidence synthesis. The most frequently investigated lower body isometric multi-joint tests for validity were the isometric mid-thigh pull and isometric squat. The validity of each of these tests was strong in terms of reliability and construct validity. The evidence for responsiveness of tests was found to be moderate for the isometric squat test and unknown for the isometric mid-thigh pull. No tests using the isometric leg press met the criteria for inclusion in the best evidence synthesis. Conclusions Researchers and practitioners can use the isometric squat and isometric mid-thigh pull with confidence in terms of reliability and construct validity. Further work to investigate other validity components such as criterion validity, smallest detectable change and responsiveness to resistance exercise interventions may be beneficial to the current level of evidence.